Growth of Arenga Palm (Arenga palmga pinnata (Wurmb) Merr.) Explant with Benzyl Amino Purine (BAP) Application - Nurmayulis, Nurmayulis; Susiyanti, Susiyanti; Kartina, Kartina (AGRIVITA, Journal of Agricultural Science, 2011)
The research was aimed to obtain the optimum concentration of BAP to buds growth as in vitro. It was conducted in the Tissue Culture Laboratory at Forestry and gardening seedling Unit of Forestry and Gardening Office of Banten Province from April until December 2008. The research used Randomized Completely Design on MS base medium with different BAP concentration: (1) B1 = MS + Kinetin 0.1 ppm + BAP 1 ppm, (2), B2 = MS + Kinetin 0,1 ppm + BAP 2 ppm, (3) B3 = MS + Kinetin 0,1 ppm + BAP 3 ppm, (4) B4 = MS + Kinetin 0,1 ppm + BAP 4 ppm, (5) B5 = MS + Kinetin 0,1 ppm + BAP 5 ppm. Each treatment was replicated ten times. The data was analyzed and continued with Duncan Multiple Range Test (DMRT) 5 percent. The explant which grew in MS media with different BAP concentration showed radicle appearance. It tended to grow to be embryo, where it began with radicle length and was followed by bud formation. Higher BAP application for each treatment increased the germination. The best concentration of embryo germination which would be grown to be bud was 4 or 5 ppm BAP. Keywords : tissue culture, Arenga palm, BAP